Pengaruh Bangtan Sonyeondan (BTS) sebagai Celebrity Endorser terhadap Brand Image E-Commerce Tokopedia - Hamdani, Tasya Camila (Jurnal Ilmu Komunikasi, 2024)
One of marketing communication strategy that is mostly done by advertisers is using celebrity endorsers. The selection of celebrity endorsers must be adjusted to the character to be built from the advertised product. The purpose of this study is to explain the effect of BTS (Bangtan Sonyeondan) as a celebrity endorser on Tokopedia’s e-commerce brand image. This research used quantitative research method with positivistic approach. Meanwhile, the type of research used in this research is explanatory research. The sample used was 96 respondents using purposive sampling technique, where only people who met the criteria were sampled. The results of this study indicate that there is a significant influence between celebrity endorsers on brand image. In addition, the results of this study note the value of the adjusted coefficient of determination (R2 adjusted) in this study is 0.367. This means that the influence of the celebrity endorser (X) on brand image (Y) is 36.7%. While the remaining 63.3% is influenced by other variables that not discussed in this study.